Distribution and Molecular Characterization of Staphylococcus aureus Isolates from Outpatient Females with Acute Urinary Tract Infection - Aya M. Radhi; Sareaa M. Al‐Mayahie (International Journal of Medical Toxicology and Legal Medicine, 2025)
Urinary tract infections (UTIs) are common and recurrent among women.Therole of Staphylococcus aureus (S. aureus) as uropathogen is rare and not well documented in young women. Hence, this study was designed for determiningprevalence of S. aureusamong young outpatient womenwith acute UTI and detecting its superantigens' genes, mecA-mediated methicillin resistance, and resistance to some antimicrobials.Out of 137 outpatient women (18-40 years old), only 7 cases (5.1%) were positive forS. aureus (4 from nonpregnant and3 from pregnant women). In addition, six (85.7%) of these isolates were associated with recurrent UTI (RUTI). Five (71.4%) of theseisolates were positive for one or more of classic enterotoxins' genes (sea-see), whereas none of them had tstor epidermolytic toxins (eta, etb, and etd). In order, see (57.1%)was the most prevalent followed by sea(42.8%), and seb(28.5%). Whereas, sec and sedwere not found in any isolate. In three cases these toxins' genes occurred in combination (sea+see; sea+seb+see; and seb+see). mecA genewas found in five isolates (71.4%).Also, 85.7% and 57.1% of the isolates wereresistantto penicillin and cefoxitin, respectively. Whereas, resistance to norfloxacin and trimethoprim was 28.5% each, and ciprofloxacin and gentamicin was 14.2% each. However,nitrofurantoin had complete activity against all of theseisolates.In conclusion, the distribution of uropathogenicS. aureus among pregnant and nonpregnant outpatient females was low but the riskof infection with this bacterium still seriousbecause of their high possession of genesof enterotoxinsand mecA and also their relationship with RUTI.